Placental miR-1301 is dysregulated in early-onset preeclampsia and inversely correlated with maternal circulating leptin - Weedon-Fekjær, MS; Sheng, Y; Sugulle, M; Johnsen, G; Herse, F; Redman, C; Lyle, R; Dechend, R; Staff, A (W.B. Saunders Ltd, 2014)
Introduction miRNAs are small non-coding RNAs important for the regulation of mRNA in many organs including placenta. Adipokines and specifically leptin are known to be dysregulated in preeclampsia, but little is known regarding their regulation by miRNAs during pregnancy. Methods We performed high-throughput sequencing of small RNAs in placenta from 72 well-defined patients: 23 early-onset preeclampsia (PE), 26 late-onset PE and 23 controls. The regulation of some miRNAs was confirmed on qRT-PCR. Maternal circulating levels and placental mRNA of leptin, resistin and adiponectin were measured using Bio-Plex and qRT-PCR. Results We found that miR-1301, miR-223 and miR-224 expression was downregulated in early-onset PE, but not in late-onset PE, compared to controls. In silico analysis predicted the leptin gene (LEP) to be a target for all three miRNAs. Indeed, we found significant correlation between maternal circulating levels of leptin and placental LEP expression. In addition, we found a significant inverse correlation between maternal circulating leptin/placental LEP expression and placental miR-1301 expression levels. Interestingly, placental expression of miR-1301 was also correlated with newborn weight percentile and inversely correlated with both maternal systolic and diastolic blood pressure prior to delivery. Discussion Our results confirm that placenta is a major site of LEP expression during pregnancy. It further suggests that miR-1301 could be involved in the regulation of leptin during pregnancy and may play a role in early-onset PE. Conclusions miR-1301 is dysregulated in early-onset preeclampsia and could possibly play a role in the regulation of leptin during pregnancy. © 2014 Elsevier Ltd. All rights reserved.